Tessier number 30 - G. Senan Manesh; kumar Padma; K. T. Jisha (Indian Journal of Plastic Surgery)
Group 30 cleft of Tessier classification of craniofacial clefts is supposedly one of the rarest clefts seen. This case presented in a most interesting and bizarre fashion - a neck swelling becoming prominent on coughing. The associated finding was even more amazing and rare - a congenital foregut duplication cyst in the neck. We proceed to discuss the rarity of such a case and the possibility of this being one of first few of its kind.